Adsorption of Cd (II) ions and methyl violet dye by using an agar-graphene oxide nano-biocomposite - Felipe Melo Lima Gomes, Brener (Environmental technology, 2024)
In this work, an agar-graphene oxide hydrogel was prepared to adsorb Cd (II) and Methyl Violet (MV) from water. The hydrogel was synthesised and characterised through SEM and EDS. Kinetic, equilibrium and regeneration studies were carried out, in which Langmuir, Freundlich and Sips isotherm models were fitted to the equilibrium experimental data; and regarding the kinetics, studies were conducted by modelling experimental data considering both empirical and phenomenological models. SEM and EDS have shown the composite present a 3D-disordered porous microstructure and that it is mainly constituted of C and O. Sips model fitted well to Cd (II) (R2 = 0.968 and χ2 =  0.176) and MV (R2 = 0.993 and χ2 =  0.783). The qmax values for MV and Cd (II) were 76.65 and 11.70 mg.g-1, respectively. Pseudo-order models satisfactorily described Cd (II) and MV adsorption kinetics with R2 > 0.90. Regeneration experiments revealed an outstanding reuse capacity of the adsorbent after three cycles of adsorption-desorption for both Cd (II) and MV. This study evidences the possibility of a feasible adsorbent for Cd (II) and MV removal from water for successive cycles of use